A Study on the Level of COVID-19 Pandemic Fatigue Among Pre-University Students at ASASIpintar UKM - Ong, Ting Wen; Nasuhah Mohd Nor; Yuhana I’liyani Rahmat; Lim, Zi Yi; Ilya Adlina Abdul Halim; Nor Azah Nik Jaafar (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study examined the level of COVID-19 pandemic fatigue among pre-university students from ASASIpintar UKM. A total of 118 students participated in a survey conducted online from February to March, 2022. The survey questionnaire consists of three parts, namely Part A, B and C. Part B served as the main assessment tool to measure the level of pandemic fatigue. It was found that at least 8 out of every 10 students suffered mild to moderate level of pandemic fatigue. Out of a total 118 respondents, 8 students (6.8%) were categorized under severe level. The level of fatigue was shown to be not dependent on gender and respondent’s history of covid infection. The outcome of this study implied the need for education providers to alleviate students’ unpleasant experience under the lockdown environment by devising context-specific methods during online learning which itself posed many challenges to the students. The results of this study may possibly imply of a generic situation that prevails among students at higher learning institutions during this pandemic era. Keyword: COVID-19, pandemic fatigue, lockdown, pre-university students, higher education institutions